2022
DOI: 10.3390/foods11111563
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Fatty Acids Affected Their Derivative Volatiles during Tieguanyin Tea Processing

Abstract: Fatty acids (FAs) are important precursors of oolong tea volatile substances, and their famous derivatives have been shown to be the key aroma components. However, the relationship between fatty acids and their derivatives during oolong tea production remains unclear. In this study, fresh Tieguanyin leaves were manufactured into oolong tea and green tea (control), and fatty acids and fatty acid-derived volatiles (FADV) were extracted from processed samples by the sulfuric acid–methanol method and solvent-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…In contrast, cis -3-hexenyl hexanoate was positively correlated with cis -jasmone (R = 0.85) ( Figure 6 b). Considering that hexadecenoic acid (16:1) is present in fresh tea leaves at an appreciable amount (~59 μg g −1 fresh weight) [ 83 ], these negative correlations raise an open question regarding whether hexadecenoic acid could be oxidized into hexanol, hexanate, or cis -jasmone in tea plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, cis -3-hexenyl hexanoate was positively correlated with cis -jasmone (R = 0.85) ( Figure 6 b). Considering that hexadecenoic acid (16:1) is present in fresh tea leaves at an appreciable amount (~59 μg g −1 fresh weight) [ 83 ], these negative correlations raise an open question regarding whether hexadecenoic acid could be oxidized into hexanol, hexanate, or cis -jasmone in tea plants.…”
Section: Resultsmentioning
confidence: 99%
“…The MVA volatile synthesis pathway and fatty acid-derivative pathway are the two minor pathways contributing to the total fresh tea leaf volatile contents ( Table 1 ). However, they also make significant contributions to tea’s aroma characteristics [ 83 ]. The positive correlations between the MVA volatile synthesis pathway and the fatty acid-derivative pathway ( Figure 2 a) provide opportunities to simultaneously increase their contents and breed new tea germplasms with higher aroma quality.…”
Section: Discussionmentioning
confidence: 99%
“…According to the discrete degree of F_v_T3 and F_v_CK3 in the load diagram, we could infer that the participation of the mechanical force is an important factor in promoting the change in the principal components of FAs [30]. The FAs screened under the condition that vip >1.0 reflected that the change in fatty acid carbon chain is more obvious than the change in saturated bond [31,32]. The activity of LOX in turnover tea leaves was significantly higher than that in spreading leaves, suggesting that the LOX were significantly enhanced by the mechanical wounding.…”
Section: Change In Fas During the Postharvest Process Of Oolong Tea P...mentioning
confidence: 99%
“…Different to traditional black tea, the processing methods of innovative black tea ad ditionally include turning over after the withering period (Figure 1), a method initially originating from the processes used for oolong tea. It was found that during the turning over period, the aromatic volatile compounds formatted and accumulated, finally contrib uting to the floral and fruity aroma of the processed tea [17,18]. Moreover, innovative black tea tends to be processed with aroma-enriched tea cultivars, such as Camellia sinesi cv.…”
Section: Introductionmentioning
confidence: 99%